Simple vs complex congenital nasolacrimal duct obstructions: etiology, management and outcomes. Issue 2 (3rd November 2014) - Ali, Mohammad Javed; Kamal, Saurabh; Gupta, Adit; Ali, Mohammad Hasnat; Naik, Milind N.
<x xml:space="preserve">Abstract</x> Background The aim of this study was to report the comparative clinical profiles and outcomes of simple and complex congenital nasolacrimal duct obstruction (CNLDO). Methods The study was a retrospective chart review of all patients presenting with CNLDO from a single surgeon's (M.J.A.) database. All patients underwent irrigation and probing under nasal endoscopic guidance. A detailed lacrimal system evaluation was performed, intraoperative findings including nasal endoscopy were documented, and etiologies of complex CNLDO were noted. Outcome measures were comparative profiles, and anatomical success and functional success of the interventions. Statistical analyses were performed using the Shapiro‐Wilk test, Fisher's exact test, and Wilcoxon rank sum test. Results Ninety‐five eyes of 81 patients with simple CNLDO and 100 eyes of 83 patients with complex CNLDO were compared. The mean age at presentation was 17.6 months in simple CNLDO and 45.6 months in complex cases (p < 0.001). Epiphora and discharge were the most common symptoms; 89.4% among simple cases and 92% in the complex group. The most common causes of complex CNLDO were bony obstructions (23%), craniofacial syndromes (12%), and buried probe (10%). At a mean follow‐up of 5.85 months for simple CNLDO and 4.68 months for complex CNLDO, anatomical success and functional success was noted in 97.8% and 94.7%, respectively, in simple CNLDO, and in 58% and 51%, respectively, in complex CNDLO (p < 0.001). Conclusion Bony obstruction, craniofacial syndrome, and buried probe were the most common reasons for a complex CNLDO, noted commonly in older children, with irrigation and probing having much poorer outcomes when compared with simpler obstructions.